A Beautiful Failure: The Tragic—And Luminous—Life of Jim Harvey (An Experiment in Narrative Theology) - Elwell, J. Sage (Religions, 2022)
Jim Harvey was the artist who created the Brillo box that Andy Warhol copied and made famous. Warhol’s Brillo Boxes changed the course of art history and the entire field of aesthetics and the philosophy of art. Meanwhile, Jim Harvey died a failed second-generation Abstract Expressionist. To his death, Harvey refused to accept that his Brillo box was a work of art. However, the theory—the story—that was woven about Warhol’s Brillo Boxes transformed them from commonplace objects into multimillion-dollar masterpieces. As a counterbalance, this article appeals to narrative theology as a way to tell Jim Harvey’s story. Appealing to narrative theologian James McClendon’s notion that a biography can reveal an image—a metaphor—that serves as a prism through which that individual’s life can be seen and understood, this article suggests that the defining metaphor of Jim’s life was "artists are prophets". Importantly, this essay is not an attempt to redeem Harvey’s artistry, although it may provoke a reconsideration of his work. Rather, it is an exploration of the tragic and luminous life of a beautiful failure.